2012
DOI: 10.1523/jneurosci.0225-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

NMDARs Mediate the Role of Monoamine Oxidase A in Pathological Aggression

Abstract: Converging evidence shows that monoamine oxidase A (MAO A), the key enzyme catalyzing serotonin (5-hydroxytryptamine; 5-HT) and norepinephrine (NE) degradation, is a primary factor in the pathophysiology of antisocial and aggressive behavior. Accordingly, male MAO A-deficient humans and mice exhibit an extreme predisposition to aggressive outbursts in response to stress. As NMDARs regulate the emotional reactivity to social and environmental stimuli, we hypothesized their involvement in the modulation of aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 80 publications
8
50
0
Order By: Relevance
“…This study revealed stress-induced increases in the hippocampal expression of NR2A and the NR2A/NR2B ratio ( Figure 3A, C), which were previously shown to accompany elevated anxiety (Boyce-Rustay & Holmes, 2006;Calabrese et al, 2012;Gao et al, 2010), impulsivity and aggression (Bortolato et al, 2012;Meyer et al, 2004), home cage hyperactivity and a stress-induced increase in peripheral concentrations of corticosterone (Huang et al, 2010;Longordo et al, 2009) in various conditions. A limitation of our study, however, is the need for confirmation that the mRNA changes result in corresponding changes in subunit protein levels and in altered synaptic function in the hippocampus.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This study revealed stress-induced increases in the hippocampal expression of NR2A and the NR2A/NR2B ratio ( Figure 3A, C), which were previously shown to accompany elevated anxiety (Boyce-Rustay & Holmes, 2006;Calabrese et al, 2012;Gao et al, 2010), impulsivity and aggression (Bortolato et al, 2012;Meyer et al, 2004), home cage hyperactivity and a stress-induced increase in peripheral concentrations of corticosterone (Huang et al, 2010;Longordo et al, 2009) in various conditions. A limitation of our study, however, is the need for confirmation that the mRNA changes result in corresponding changes in subunit protein levels and in altered synaptic function in the hippocampus.…”
Section: Discussionsupporting
confidence: 68%
“…In the present experiment, mRNA expression of NR2B and the NR1 in the hippocampus was not significantly changed by stress (Figure 3). However, previous work has reported a significant decrease in NR2B expression in several brain areas during stress (Cull-Candy et al, 2001;Huang et al, 2010), aging (Dere et al, 2003) and compromised plasticity (Bortolato et al, 2012). Previous work has also reported a decrease in NR1 mRNA after stress (Cull-Candy et al, 2001;Schenberg et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…As in humans, disruption of the MAOA gene in either a C3H/He or 129S6 mouse genetic background escalated aggressive behavior in males such as infliction of skin wounds on cage mates and short attack latency in the resident-intruder test (Cases et al, 1995; Scott et al, 2008). In addition to large increase of 5-HT and norepinephrine, which are normally degraded by MAOA, in the developing brain, MAOA knockout mice showed altered expression of the NMDA receptor subunits in the PFC; higher expression of NR2A and NR2B subunits as well as reduced levels of glycosylated NR1 compared with those in wild-type mice (Bortolato et al, 2012). These alterations reduced NMDA-mediated fluctuations in the amplitude and decay time of excitatory postsynaptic current (EPSC) in the PFC, and a moderate dose of dizocilpine or antagonists for either NR2A or NR2B reduced aggressive behavior in MAOA knockout mice without affecting locomotion (Bortolato et al, 2012).…”
Section: Excitatory and Inhibitory Neurotransmission And Aggressionmentioning
confidence: 99%
“…In preliminary data, we found that treatment with low, intrinsically ineffective doses of apomorphine, a non-selective dopaminergic agonist, induced a significant increase in stereotyped behaviors in MAO A KO mice (Godar and Bortolato, unpublished observations). Although neither MAO A KO nor hypomorphic mice exhibit spontaneous PPI deficits, both lines are hyperresponsive to the PPI-disruptive properties of NMDA glutamate receptor antagonists in this paradigm (Godar and Bortolato, unpublished observations), possibly reflecting alterations in the subunit composition of this receptor in the prefrontal cortex (Bortolato et al, 2012). Of note, MAO A KO mice feature a prominent disruption of somatosensory cortex (Cases et al, 1995), possibly suggesting a template for the neuroanatomical alterations of this region in TS patients.…”
Section: Animal Models Based On Genetic Manipulationsmentioning
confidence: 99%